Dental Application of Natural Products - Sakagami, Hiroshi (Medicines (Basel), 2018)
This review article summarizes the recent progress in dental applications of natural products. Catechin gel showed selective antimicrobial activity, whereas the alkaline extract of various plant species rich in lignin carbohydrate complex (LCC) showed much higher antiviral activity than lower molecular weight polyphenols. Mouthwash with the alkaline extract of a plant classified as OTC effectively reduced halitosis. Unexpectedly, many polyphenolic compounds purified from the natural kingdom showed much lower tumor-specificity against human oral squamous cell lines as compared with antitumor agents, although they showed apoptosis-inducing activity. The alkaline extract of bamboo leaf, which exerted various common biological activities with LCC, showed osteogenic activity by stimulating differentiation toward osteoblasts while inhibiting differentiation toward osteoclasts. LCC enhanced the dectin-2 mRNA expression in macrophages, whereas glucan showed anti-osteoblastic action via dectin-1. These data suggest that natural products exert their biological activity by interacting with these molecules.